PENGARUH VARIASI REMPAH DENGAN BERBAGAI KONSENTRASI PADA SUSU KEDELAI TERHADAP PENERIMAAN KONSUMEN - Nurwidah, Andi; Rabiah, Rabiah; Nurwilda, Nurwilda; Ismaizura, Nur (Jurnal Teknologi Pengolahan Pertanian, 2024)
Soy milk is a drink that has high nutrition, especially because of its protein content. Soybeans have a protein content of around 35%, even in superior varieties, the protein content can reach 40-43% (Margono et., al. 2000). Apart from that, soy milk also contains fat, carbohydrates, calcium, phosphorus, iron, pro-vitamin A, vitamin B complex (except B12) and water. The aim of this research is to determine the effect of adding a variety of spices (cloves (Syzygium aromaticum), nutmeg (Myristica fragrans)) and cinnamon (Cinnamomum verum)) with different concentrations in making soy milk. Based on the results of organoleptic tests that were carried out on samples with the addition of 2% spices, it was found that the average level of panelists' liking was higher in the SK 4 (cinnamon) samples with values for color (3.72), taste (3.62), aroma (3.72), and texture (3.76). Meanwhile, the results of the organoleptic test on samples with the addition of 3% showed that the average level of preference for the panelists was color SK 2 (3.56), taste SK (3.61), aroma SK (3.57), and texture SK (3 .76).